2006
DOI: 10.1080/08035250500537017
|View full text |Cite
|
Sign up to set email alerts
|

End‐tidal carbon monoxide measurements in infant respiratory distress syndrome

Abstract: During severe RDS, inflammation may contribute to increased lipid peroxidation leading to increased local CO production in the lung, indicated by increased ETCOc. Early ETCOc determinations may be helpful to exclude occurrence of chronic lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 23 publications
4
27
1
Order By: Relevance
“…Simultaneously, blood was sampled for MDA, IL-6 and IL-8. The method to measure ETCOc was described previously [6,16,17] . Briefly, this noninvasive bedside instrument uses electrochemical sensors for measurement of CO, and an infrared optical bench for measurement of end-tidal carbon dioxide.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, blood was sampled for MDA, IL-6 and IL-8. The method to measure ETCOc was described previously [6,16,17] . Briefly, this noninvasive bedside instrument uses electrochemical sensors for measurement of CO, and an infrared optical bench for measurement of end-tidal carbon dioxide.…”
Section: Methodsmentioning
confidence: 99%
“…The higher ETCOc values in these infants compared with the values in infants without hsPDA suggest the presence of a vasodilatory circulatory state. Since earlier studies already revealed an association between severe RDS and increased values for ETCOc [10], it is conceivable that the infants are in a pro-inflammatory state, resulting in preterm birth, severe RDS and development of hsPDA. However, the vasodilatory state could not be confirmed by higher blood pressure support scores in these infants.…”
Section: Discussionmentioning
confidence: 99%
“…In infants with spontaneous ventilation the nasal sampler was inserted approximately 5 mm into the nostril. In case of mechanical ventilation the sampler was inserted into the proximal part of the endotracheal tube via a T-connector [10]. With the COCO 2 Puff, a device comparable to the Natus CO-Stat™ End Tidal Breath Analyzer (Natus Medical, Inc., San Carlos, Calif., USA) ETCOc, ETCO 2 and ventilatory rate were measured non-invasively at the bedside [7].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations